(untitled) (Coordinates of Public Administration, 2026)
The article, based on an analysis of the current state and the relevant regulatory and legal framework, scientific literature on the research problem, shows that the socio-psychological socialization of internally displaced persons (IDPs) requires new research, given the almost four-year-long Russian-Ukrainian war, which continues to create new problems in the context of the socio-psychological socialization of IDPs. The scale of the IDP problem (including children, people of working age, people with special needs, etc.) stimulates the study of the socialization of IDPs in the context of armed aggression and mass population displacement in Ukraine. In this regard, psychological consequences are of particular importance, primarily traumatic experiences, loss of familiar surroundings, impact on identity and mental health, etc. Special emphasis is needed on social integration, i.e. the importance of successful socialization for the sustainability of host communities and national unity. Of particular note is the research into the socio-psychological problems of IDPs: psychological distress (PTSD, anxiety, depressive states, feelings of guilt), identity problems (loss of the «small homeland», formation of a new «self-concept» and group identity), intergroup relations (stereotypes and prejudices between IDPs and the host community, risks of social tension). Legislative protection of the rights and freedoms of IDPs is also of paramount importance, primarily the proper implementation of the Law of Ukraine «On Ensuring the Rights and Freedoms of Internally Displaced Persons», systematic work of state authorities and local self-government bodies (LSGs), practice of work of public and international organizations, First of all, the application of cases of successful psychosocial support, educational and economic programs (UNICEF, UNHCR, Red Cross, etc.), the application of advanced European experience in the socialization of IDPs.